POLITICAL TRANSFORMATION OF TURKEY IN THE CONTEXT OF THE REFERENDUM ON 16 APRIL - D. B. MALYSHEVA (Контуры глобальных трансформаций: политика, экономика, право, 2017)
The article deals with the peculiarities of the transformation of  Turkey in the sphere of internal and foreign policy in the light of the  referendum held on April 16, 2017 on the issue of the extension of  powers of the head of state. The preconditions and consequences of  the transition of Turkey from a parliamentary political system to a presidential one are analyzed, as well as the problem of stability of  the internal political situation in the republic in the conditions of the economic crisis, the unresolved Kurdish problem, the increase  of terrorist threat. In the article the changes in the positioning of Turkey in the international arena appeared after the referendum,  in particular in the relations with the European Union which Turkey  has tried to join for a long time are revealed. Special attention is  paid to the international and political activity of Turkey in the Middle East region and in the Syrian conflict zone where the military  confrontation sparked the activation of radical Islamist movements  and terrorist structures. The evolution of the Turkish approaches to the crisis in Syria is analyzed, the role of Turkey which with Russia  and Iran has become a guarantor of peaceful settlement  within the framework of Astana process is estimated. Based on the  analysis of the peculiarities of the transformation of Turkey as a  regional power a conclusion is made about the postreferendum continuity of the political course in the sphere of internal and foreign policy and that within the framework of the  presidential political system developing in the republic one can  expect greater dynamics in the adoption of economic, political and  international solutions.